Effectiveness of Providing Supplementary Food for Stunted Toddlers in Indonesia: A Literature Review - Bandur, Paskalinda Maria Yosefa; Madur, Junita Putriawan (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2025)
Stunting is a global nutritional issue and remains a significant health challenge in Indonesia. Although the prevalence of stunting in Indonesia has shown a downward trend, it has not yet met the national target. The Indonesian government has implemented various programs to prevent stunting, including the provision of supplementary food for stunted toddlers. This study aims to assess the effectiveness of supplementary food interventions for stunted toddlers in Indonesia. The research design is a literature review, with articles sourced from the PubMed and Google Scholar databases using the PRISMA method. Articles selected met predefined inclusion and exclusion criteria, resulting in a total of 10 journal articles published between 2020 and 2024. The results indicated that 9 articles reported improvements in height and weight among stunted toddlers following the intervention, suggesting that supplementary food is an effective measure. One article reported that the provision of supplementary food did not significantly increase height. The types of supplementary food used included both instant products and those made from local ingredients. The conclusion indicates that supplementary feeding programs in Indonesia have been implemented effectively.